DETERMINATION OF ANTIOXIDANT ACTIVITY IN OIL AND RED FRUIT JUICE (Pandanus conoideus Lamk) WITH DPPH METHOD - Ees Aisyah Al failah; Rizki Febriyanti; Wilda Amananti (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2024)
Antioxidant compounds play an essential role in health because they can reduce the risk of chronic diseases such as cancer and coronary heart disease. This study analyzed the antioxidant activity of red fruit oil and juice. This study used an experimental method with oil and juice obtained through boiling for 4-5 hours. The stages of the study include flavonoid qualitative tests and antioxidant activity tests using the DPPH method using UV-Vis Spectrophotometers. Based on the research results, oil and red fruit juice contain flavonoids that have the potential to be antioxidants. Antioxidant activity test with the DPPH method showed IC50 in red fruit oil products on the market at 30.11 ppm and red fruit juice at 31.80 ppm, showing vigorous antioxidant activity compared to homemade red fruit oil with an IC50 of 85.98 ppm.